Study on A.C properties of tin selenidethin films - Sakrani, Samsudi; Othaman, Zulkafli; Deraman, Karim; Wahab, Yussof (Faculty of Science, Universiti Teknologi Malaysia, 2008)

(untitled)
A.c properties of tin selenide thin films prepared by an encapsulated selenization method are investigated. The measurements obtained from al/snse/al sandwich structures showed strong indication of frequency and temperature dependence of capacitance, dielectric loss and conductance over the ranges of 5-200 khz and 228-373 k, respectively. Dielectric behaviour was expected to be due to space charge polarization which contributed to a.c conduction. This was generally explained in terms of hopping of the charge carriers between localized states with activation energies 0.03-0.08 ev. Parameters such as trap binding energy (0.94 ev) and minimum hopping distance (1.01 nm) were also predicted